Experimental evidence on structural adequacy of high strength S690 steel welded joints with different heat input energy. (1st February 2020) - Chung, Kwok-Fai; Ho, Ho-Cheung; Hu, Yi-fei; Wang, Kai; Liu, Xiao; Xiao, Meng; Nethercot, David A.
Highlights: Adverse effects of welding on mechanical properties of high strength S690 steel welded joints are quantified. Experimental evidence on structural adequacy of these S690 welded joints is provided. Pilot tests on 18 coupons of S690 welded joints under tension were conducted to examine their deformation characteristics. 12 reference and 12 spliced S690 welded H-sections with different heat-input-energy were tested under compression. By proper control on heat-input-energy during welding, little or no reduction in the mechanical properties of S690 welded joints is found. Abstract: Quenching and tempering is a highly developed heat treatment method to produce high strength steels with certain quantities of expensive alloy elements. This process has been highly industrialized and widely adopted in modern steel mills to produce high strength S690 steels. However, a heating/cooling cycle induced during welding may initiate phase transformation, re-crystallization and grain growth in microstructures of these steels. This will cause a significant reduction in their mechanical properties if both the maximum temperatures during welding and the cooling rates after welding are not properly controlled. Over the past twenty years, conflicting research findings have been reported on mechanical properties of these S690 welded sections due to different welding procedures and parameters adopted during welding. In order to quantify adverse effects on mechanical properties of the S690 steel welded joints under static loads, a series of pilot tests on a total of 18 coupons of S690 steel plates, welded joints and weld metals with different heat input energy during welding have been conducted to examine their deformation characteristics under tension. Moreover, 12 reference and 12 spliced S690 welded H-sections with different heat input energy adopted in the welding processes have been conducted to examine their deformation characteristics under compression, in particular, their section resistances under compression. It is demonstrated that by a proper control on the heat input energy during welding, it is possible to control or even eliminate any reduction in the mechanical properties of these S690 welded joints under either tension or compression. Consequently, experimental evidence on structural adequacy of these high strength S690 steel welded joints with different heat input energy adopted in the welding processes is provided scientifically to confirm applications of these high strength S690 steels in construction.